2003
DOI: 10.1034/j.1600-0463.2003.1110204.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary thrombosis and sudden death after an enteroviral infection

Abstract: We report the case of a 26-year-old man who died suddenly 9 days after an episode of flu. Microscopic examination of the left anterior descending coronary artery showed an eccentric fibroatheromatic plaque complicated by thrombosis, endothelial erosion and extensive T-cell and macrophage infiltration. Frozen sections of the thrombotic coronary segment, analysed for different infective agents by polymerase chain reaction (PCR) and reverse transcriptase (RT)-PCR, showed positive amplification for an enteroviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…[ 104 ] Another case with myocardial infarction due to coronary thrombosis was reported, wherein enterovirus was detected postmortem both in the coronary atherosclerotic plaque and in heart tissue. [ 105 ] Similarly, in a third case, presumed myopericarditis co-occurred with coronary angiography and CMR proven acute posterior myocardial infarction, related to a right coronary artery thrombosis, and a concurrent Coxsackievirus B2 infection. [ 106 ] Furthermore, we have recently shown in autopsied cases of patients diagnosed postmortem with lymphocytic myocarditis a high prevalence of very recent myocardial infarction, some with thrombus-occluded coronary arteries.…”
Section: Effects On Coronary Artery Atherosclerosismentioning
confidence: 99%
“…[ 104 ] Another case with myocardial infarction due to coronary thrombosis was reported, wherein enterovirus was detected postmortem both in the coronary atherosclerotic plaque and in heart tissue. [ 105 ] Similarly, in a third case, presumed myopericarditis co-occurred with coronary angiography and CMR proven acute posterior myocardial infarction, related to a right coronary artery thrombosis, and a concurrent Coxsackievirus B2 infection. [ 106 ] Furthermore, we have recently shown in autopsied cases of patients diagnosed postmortem with lymphocytic myocarditis a high prevalence of very recent myocardial infarction, some with thrombus-occluded coronary arteries.…”
Section: Effects On Coronary Artery Atherosclerosismentioning
confidence: 99%
“…Several published reports have demonstrated the molecular detection of EV ribonucleic acid (RNA) genomes in myocardial tissues of patients with end-stage cardiac chronic coronary diseases requiring heart transplantation (14,15). Moreover, the EV genome was detected in sections of thrombotic coronary segment of a young patient who died suddenly of acute MI (16), whereas another study identified the presence of EV RNA in 17% of 128 atherosclerotic plaque samples, but not in any of the 20 normal arterial wall samples (17). Taken together, these findings suggest that EV infection of cardiovascular tissues may play a role in the pathogenesis of coronary disease leading to MI.…”
mentioning
confidence: 98%
“…Enterovirus could also have a significant tropism for the endothelium and behave like an innocent bystander without any part in the development of atherosclerotic lesions. Of note, enterovirus were detected in atherosclerotic plaque as partial genomic fragments (Calabrese et al, 2003;Kwon et al, 2004;this study) and the presence of replicating and infectious particles has not been investigated. Further prospective studies are needed on a larger population of patients in comparison to appropriate controls to confirm the involvement of enterovirus in the atherogenesis process.…”
Section: Discussionmentioning
confidence: 89%
“…1). However, in contrast to what assessed by others (Calabrese et al, 2003;Kwon et al, 2004), nucleotide sequencing of the 5 UTR of enterovirus do not allow genotyping because of the high conservation of this part of the viral genome (Muir et al, 1998). To date, our attempts to amplify the VP1 coding region from the vascular samples found positive by nested RT-PCR in the 5 UTR failed, rendering not possible the identification of the enterovirus strains at the genotype level.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation